2006
DOI: 10.1038/sj.emboj.7601057
|View full text |Cite
|
Sign up to set email alerts
|

Axin is a scaffold protein in TGF-β signaling that promotes degradation of Smad7 by Arkadia

Abstract: TGF‐β signaling involves a wide array of signaling molecules and multiple controlling events. Scaffold proteins create a functional proximity of signaling molecules and control the specificity of signal transduction. While many components involved in the TGF‐β pathway have been elucidated, little is known about how those components are coordinated by scaffold proteins. Here, we show that Axin activates TGF‐β signaling by forming a multimeric complex consisting of Smad7 and ubiquitin E3 ligase Arkadia. Axin dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
152
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 48 publications
1
152
2
Order By: Relevance
“…Smurf1 and Smurf2 bind to the PY motif in the Smad7 linker region and ubiquitinate Smad7, and this action may be direct, as shown by in vitro ubiquitination experiments [23,24,73]. Alternatively, the discovery that Arkadia plays a primary role in Smad7 polyubiquitination and proteasomal degradation [74,75] is compatible with a model whereby Smurfs bound to Smad7 might ubiquitinate another protein that eventually activates Arkadia, which leads to the degradation of Smad7. Whether other Smad7-bound E3 ligases such as WWP1 and NEDD4-2 participate in a similar regulatory loop remains to be clarified [32].…”
Section: Regulation Of Stability Of I-smads and Other Signaling Targetsmentioning
confidence: 83%
See 1 more Smart Citation
“…Smurf1 and Smurf2 bind to the PY motif in the Smad7 linker region and ubiquitinate Smad7, and this action may be direct, as shown by in vitro ubiquitination experiments [23,24,73]. Alternatively, the discovery that Arkadia plays a primary role in Smad7 polyubiquitination and proteasomal degradation [74,75] is compatible with a model whereby Smurfs bound to Smad7 might ubiquitinate another protein that eventually activates Arkadia, which leads to the degradation of Smad7. Whether other Smad7-bound E3 ligases such as WWP1 and NEDD4-2 participate in a similar regulatory loop remains to be clarified [32].…”
Section: Regulation Of Stability Of I-smads and Other Signaling Targetsmentioning
confidence: 83%
“…Possibly by studying the specific timing of pathway regulation by each one of these enzymes and their adaptor proteins like Smad7. Smad7, which regulates both nuclear Smad signaling [77,78] and TGFb receptor signaling in the cytoplasm [23,24,74,75], is a key factor. Whether or not Smad7 exists in nuclear complexes together with Ski and SnoN remains currently unknown.…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
“…Here we report that increased stability of WT Myc is a prominent mechanism for Myc overexpression in breast cancer and that this is associated with a change in the ratio of phospho-S62 (pS62) and phospho-T58 (pT58) to more closely match mutant Myc that has increased oncogenic activity. Exploration into the mechanism behind the altered ratio of S62 and T58 phosphorylation in breast cancer suggests a prominent role for deregulation of the Axin1 tumor suppressor.Axin1 is a multidomain scaffold protein that coordinates several different protein complexes involved in regulating Wnt, TGFβ, SAPK/JNK, and p53 signaling (20)(21)(22)(23)(24). Recently, we found that Axin1 promotes Myc degradation and decreases levels of Myc S62 phosphorylation by coordinating the formation of a Myc destruction complex that includes GSK3β, PP2A, and other proteins involved in degrading Myc (24).…”
mentioning
confidence: 99%
“…Axin1 is a multidomain scaffold protein that coordinates several different protein complexes involved in regulating Wnt, TGFβ, SAPK/JNK, and p53 signaling (20)(21)(22)(23)(24). Recently, we found that Axin1 promotes Myc degradation and decreases levels of Myc S62 phosphorylation by coordinating the formation of a Myc destruction complex that includes GSK3β, PP2A, and other proteins involved in degrading Myc (24).…”
mentioning
confidence: 99%
“…In addition to Smurfs and Smurf-like molecules the nuclear RING-domain ubiquitin ligase Arkadia has been shown to degrade Smad6/7 in cooperation with the scaffold protein Axin [104,105]. Jab1/CSN5, a component of the COP9 signalosome complex, also associates with Smad7 to cause its translocation from the nucleus to the cytoplasm and promote its ubiquitination and degradation [106].…”
Section: I-smads and T β Rsmentioning
confidence: 99%